The impact of reading at rapid rates on inference generation. (25th July 2017) - Collins, W. Matthew; Daniel, Frances
Abstract : Aims: Speed reading is advertised as a way to increase reading speed without any loss in comprehension. However, research on speed reading has indicated that comprehension suffers as reading speed increases. We were specifically interested in how processes of inference generation were affected by speed reading. Methods: We examined how reading speed influenced inference generation in typical readers, trained speed readers and participants trained to skim read passages. Passages either strongly or weakly promoted a bridging or predictive inference. After reading, participants performed a lexical decision task on either a nonword, neutral or inference‐related word. Results: Typical readers responded to strong and weak inference words faster than neutral words. There were no statistical differences in reaction time between inference‐related and neutral words for speed and skim readers. Conclusions: These findings provide no substantive evidence that the appropriate inferences are generated when reading at rapid speeds. Thus, speed reading may be detrimental to normal integrative comprehension processes.